Editorial: Progress and Prospects on Skin Imaging Technology, Teledermatology and Artificial Intelligence in Dermatology - Li, Chengxu; Mun, Je-Ho; Pasquali, Paola; Li, Hang; Soyer, H. Peter; Cui, Yong (Frontiers in Medicine, 2021)
Dermatology is an independent clinical discipline established based on cognitive features. With the emergence of digital technology, remote transmission and internet technologies, dermatology has become a very well-suited discipline to integrate these technologies and apply them in clinical practice due to its characteristics. At present, the development of skin imaging technologies (dermoscopy, reflectance confocal microscopy (RCM), optical coherence tomography OCT), etc.), teledermatology, and artificial intelligence (AI) has profoundly and comprehensively changed the nature, service model, and public recognition of dermatology (1). Skin imaging, as an important technical system in modern dermatology, continues to gain the attention of researchers and the wider community alike. In this spirit, we have proposed a research topic titled “Progress and Prospects on Skin Imaging Technology, Teledermatology and Artificial Intelligence in Dermatology” and are very pleased indeed that 9 manuscripts on the various aspects of skin imaging technology, 5 manuscripts on teledermatology and 7 manuscripts on AI in dermatology have been published under the banner of this specific research topic.